O-009 Mechanical balloon thromboembolectomy for the treatment of cerebral venous sinus thrombosis (CVT): a restropsective analysis of safety and efficacy in 65 consecutive patients. (12th July 2011) - Frei, D; Huddle, D; Bellon, R; Dooley, G
Abstract : Objective: Conventional treatment of cerebral venous sinus thrombosis (CVT) has been systemic heparinization. A variety of endovascular treatment paradigms have been described for the treatment of symptomatic CVST that has failed conventional therapy. We retrospectively evaluated the efficacy and safety of thromboembolectomy using the Fogarty balloon catheter (Edwards Lifesciences, Irvine, California, USA) for rapid revascularization of the major dural sinuses in consecutive patients over a 6-year period. Materials and Methods: A retrospective review of our Neurointerventional database over a 6-year period from January 2005 to January 2011 identified 65 consecutive patients who had undergone Fogarty balloon thromboembolectomy for the treatment of CVT. These patients with documented CVT were deemed a "failure" of conventional management (neurologic decline, hemorrhage or infarction, clot progression or sinus re-occlusion). All procedures were performed with ultrasound guided venous access of the internal jugular vein and placement of a vascular sheath. Low dose thrombolytic (1–10 mg of Tenecteplase (Genentech, South San Francisco, California, USA)) was utilized to lace the clot through a four French multisidehole infusion catheter in all but two patients (97%). Balloon thromboembolectomy was performed using either a three French or four French Fogarty balloon catheter until satisfactory revascularization was achieved. All patients were maintained on intravenous heparin during the procedure and continued on anticoagulation afterward. Procedural images, pre- and post- procedure neuroimaging and charts were reviewed by two experienced Neurointerventional surgeons. Revascularization was recorded as unsuccessful, partial or complete. Partial revascularization showed contrast wash out in the appropriate dural sinus, but non-occlusive residual clot remained present. Procedural complications were recorded. Results: Complete revascularization was achieved in 52 of 65 patients (80%). Partial revascularization was achieved in 13 of 65 patients (20%). There was one procedural complication (1.5%) (wire perforation with subdural hematoma), which resolved without neurosurgical intervention or neurological decline. The mean patient age was 36 years. 60% of patients were female. 10 patients required additional thromboembolectomy for sinus re-occlusion. Conclusion: Fogarty balloon thromboembolectomy can be a safe and effective treatment for cerebral venous sinus thrombosis in patients who have failed conventional management.